EXTENT OF AVAILABILITY AND UTILIZATION OF FINANCIAL RESOURCES IN THE ADMINISTRATION OF INTERNAL EXAMINATIONS IN PUBLIC SECONDARY SCHOOLS IN EBONYI STATE NIGERIA - Peter O. Nwafukwa; Anigbo B. Ifeyinwa; Odeh N. Bernadette; Uchewa I. Ifeoma; John Michael Nwankwo; Ogbu Joy Anulika; Christian O. Aleke (ZILLZELL MEDIA PRIMA, 2026)
The study x-rayed the extent of availability and utilization of financial resources in the administration of internal examinations in public secondary schools in Ebonyi State, Nigeria. The design of the study was a descriptive survey research design. The population of the study comprised 1,519 secondary school principals and teachers in 215 public secondary schools in both urban and rural areas of the state. Simple random sampling technique was used to select 100 principals and 500 teachers making a total of 600 respondents for the study. The instrument for data collection was a 20-item structured questionnaire developed by the researchers on a four-point scale of Very High Extent (VHE), High Extent (HE), Low Extent (LE) and Very Low Extent (VLE) response pattern weighted 4, 3, 2 and 1 respectively. The questionnaire was duly validated by three experts, two from Educational Administration and Planning and one from Educational Measurement and Evaluation, all from Ebonyi State University, Abakaliki. Using the test re-test procedure and applying the Pearson Product Moment Co-relation Co-efficient analysis, the reliability of the instrument was established at 0.76 using 10 secondary schools in Enugu State. Data collected were analyzed using mean and standard deviations. t-test statistic was used to test the hypotheses at 0.05 level of significance. Very high extent and high extent were used when the mean scores are above 2.50 and low extent when the mean scores are below 2.50. Findings of the study indicates that financial resources for the administration of internal examinations in Ebonyi State public secondary schools were available to a low extent, and that the utilization of financial resources for the procurement of examination materials for administration of internal examinations in Ebonyi State public secondary schools were to a very low extent. Based on the findings, the researchers made the following recommendations; government should involve Non-governmental Organization (NGOs), Philanthropists, Parent Teachers’ Association (PTA) and other concerned stakeholders in making financial resources available in public secondary schools in Ebonyi State.